2020
DOI: 10.1017/ice.2020.1319
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for voluntary participation in staff screening during an methicillin-resistant Staphylococcus aureus (MRSA) outbreak on a neonatal ward

Abstract: We investigated healthcare worker (HCW) behavior with regard to a voluntary methicillin-resistant Staphylococcus aureus (MRSA) staff screening during a MRSA outbreak in a neonatal ward. Avoiding MRSA transmission from HCWs to patients was the most important reason for participation. Inconvenient screening time was the most frequently cited reason for nonparticipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In an Egypt investigation, it was shown that the majority of doctors had a good attitude toward MRSA prevention [10]. When it comes to HCW attitudes, "wanting to prevent MRSA transmission from HCW to patients" and "concern about family members' health, [11]. For (98%) of the nurses in Portugal, maintaining professional hand hygiene was the most crucial step in lowering patient risk [12].…”
Section: Introductionmentioning
confidence: 99%
“…In an Egypt investigation, it was shown that the majority of doctors had a good attitude toward MRSA prevention [10]. When it comes to HCW attitudes, "wanting to prevent MRSA transmission from HCW to patients" and "concern about family members' health, [11]. For (98%) of the nurses in Portugal, maintaining professional hand hygiene was the most crucial step in lowering patient risk [12].…”
Section: Introductionmentioning
confidence: 99%